Catalogue of the Iranian Microgastrinae (Hymenoptera: Braconidae) - Gadallah, Neveen S.; Ghahari, Hassan; Peris-Felipo, Francisco Javier (Zootaxa, 2015)
In the present study, the Iranian Microgastrinae (Hymenoptera: Braconidae) fauna is summarized. It is based on a detailed study of all available published data and new material collected. In total 99 species belonging to 8 genera are from Iran: Apanteles Förster, 1862 (36 species), Cotesia Cameron, 1891 (34 species), Deuterixys Mason, 1981 (1 species), Diolcogaster Ashmead, 1900 (4 species), Microgaster Latreille, 1804 (4 species), Microplitis Förster, 1862 (11 species), Pholesetor Mason, 1981 (4 species) and Protapanteles Ashmead, 1898 (5 species) in 4 tribes (Apantilini, Cotesiini, Microgastrini and Microplitini). A faunistic list with distribution data, and host records are given. Four species are new records for the fauna of Iran: Apanteles brunnistigma Abdinbekova, 1969, A. ingenuoides Papp, 1971, Microplitis decipiens Prell, 1925 and M. marshallii Kokujev, 1898.